Theoretical thermal performance of cross-flow finned heat pipe heat exchanger used for air conditioning in surgery rooms - Nogueira, Élcio (Mechanical Engineering Advances, 2023)
The thermal efficiency of heat exchangers was applied for theoretical analysis of the thermal performance of a finned heat pipe heat exchanger (FHPHE) used as an auxiliary device to control the temperature and quality of the air conditioning in operating rooms. The theoretical analysis performed is punctual and distributed. It is divided into three aspects: analysis of the evaporator section, analysis of the condenser section, and analysis of the heat exchanger in terms of overall performance. The distributed procedure contrasts with the theoretical-experimental study, which uses the concept of thermal effectiveness (ε-NTU) for global heat exchanger analysis. The developed approach considers the number of heat pipes, the number of fins, and the flow rate variation at the inlet of the heat exchanger as fundamental parameters for determining the thermophysical quantities of interest. Theoretical values were determined for the average velocities, Nusselt numbers, thermal effectiveness, heat transfer rates, and exit temperatures. The localized theoretical-experimental comparisons are consistent, and the absolute relative error for the global heat transfer rate ranges from 0.5% to 35%.